The Effectiveness Of Using Quillbot In Improving Writing For Students Of English Education Study Program - Nurmayanti, Novita; Suryadi, Suryadi (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
Abstract: The aims of this study was to assess students' proficiency with Quillbot to compose error-free original scientific papers in English. This research is a quantitative study. One particular type of data was used for analysis in this study, and that was responses to questionnaires. As a result, it is very important that all students know this. Some students, however, still haven't learned the best method for paraphrasing. These skills can be honed through regular reading or by making use of various online tools, both free and paid. This research consisted of three stages: planning, implementation, and evaluation (through student questionnaires), all of which were carried out sequentially. The aim of this experiment was to determine whether using Quillbot would help students commit less plagiarism; however, students need to reread the tool to ensure that the meaning of the cited articles remains consistent. Students were able to take advantage of the software and find it useful to prephrase text without changing its meaning, according to survey findings submitted via google forms.